Investigating the role of age, admission systolic blood pressure, and neutrophil-to-lymphocyte ratio in predicting left ventricular hypertrophy among patients with primary hypertension - Xiaoyong Hu; Djandan Tadum Arthur Vithran; Zhaoying Yang; Ting Zou; Rui Tang; Hongjian Li (Journal of International Medical Research)
Objective In patients with primary hypertension (PH), left ventricular hypertrophy (LVH) is a critical predictor of cardiovascular events. We aimed to identify clinical and laboratory predictors of LVH in patients with PH. Methods This retrospective cohort study included 2321 patients with PH at the Fifth Affiliated Hospital of Xinjiang Medical University from December 2022 to January 2024. Patients were classified into LVH and non-LVH groups; LVH was defined as left ventricular mass index (LVMI) >115 g/m 2 for men and >95 g/m 2 for women. Univariate and multivariate logistic analysis were used to identify risk factors for LVH. Results Univariate analysis revealed significant differences between the LVH and non-LVH groups in age, sex, smoking, systolic blood pressure (SBP), neutrophil-to-lymphocyte ratio (NLR), body mass index, serum creatinine (SCr), lymphocyte count, and hypertension duration. Multivariate analysis identified age, sex, SBP, SCr, and NLR as independent risk factors for LVH. A combined receiver operating characteristic (ROC) model had an area under the ROC curve of 0.711 (95% CI: 0.68–0.74), with 75.3% sensitivity and 59.2% specificity. Conclusion Age, sex, SBP, SCr, and NLR were independent predictors for LVH in patients with PH. Our combined diagnostic model provides valuable insight for early LVH screening, aiding timely clinical intervention.